O atendimento educacional especializado no município de mossoró/rn: entre saberes e práticas - Lima, Maria Aparecida Dias (Universidade Federal Rural do Semi-Árido, 2020)
This dissertation aims to analyze practical and practical issues that are mobilized by teachers who work in Specialized Educational Service in the city of Mossoró, State of Rio Grande do Norte. We start from the following questions: what knowledge and practices are mobilized by the teachers who work in the Specialized Educational Service in this municipality? What can we identify and reflect on them? What do the teachers tell us help us to understand teaching in ESA? It is an autobiographical research in education (PASSEGGI, 2011; SOUZA, 2006), a qualitative research branch (MINAYO, 2008; BOGDAN, BIKLEN, 1994). Participate in the study of three teachers who work in the multifunctional resource rooms and a teacher who coordinates special education in the municipality. The corpus used for the analysis of three oral and one written narratives, in addition to images of teaching materials used in the ESA service. As sources were collected throughout 2019, through narrative interviews (JOVCHELOVICTH, BAUER, 2002). For theoretical foundation on Special Education in the Inclusive Education Perspective, considered current legislation (BRASIL, 2008) and experts in the area (MANTOAN, 2003; 2006; MAZZOTTA, 2005). As the narratives revealed that the ESA provides accessibility in the researched schools, it perceives (a) students with disabilities as a potential and potential, that needs bridges, of possibilities available to learn. Shown as collaborative practices, it is a significant interaction between subjects, which establishes a relationship of mutual respect between pedagogical knowledge and practices. As interdisciplinary and transdisciplinary articulations are interactive strategies or attitudes that allow access to students with disabilities in the regular classroom and mobilize other students after empathy in the learning process with human difference. The pedagogical materials are constructed according to the needs and interests of the students, configuring a very unique look, which gives meaning and meaning to the different learnings. From the construction of four axes of analysis, namely: Specialized teaching: providing accessibility to learning; use and construction of teaching resources in the multifunctional resource rooms; assessment of learning in the ESA and images and narratives to see, feel and transform. We had the possibility to analyze important aspects of teaching at AEE, in the municipality of Mossoró / RN. Finally, we learned from the collaborating teachers that listening, seeing and feeling the needs of Special Education students must be a political commitment for all educators
Keywords: Atendimento educacional especializado; Inclusão; Práticas pedagógicas; Narrativas de professoras do AEE; Specialized educational service; Inclusion; Pedagogical practices; AEE teachers' narratives; MULTIDISCIPLINAR::ENSINO